Mind mapping: Improving learning outcomes, participation and student creativity in science lessons at SDN 03 Kanigoro - Sari, Maya Kartika; Muaini, Muaini (Universitas Riau Kepulauan, 2024)
This research aims to analyze the increase in learning outcomes, student participation, and student creativity in science and science subjects through the Mind Mapping method at SD Negeri 03 Kanigoro Madiun. This type of research uses classroom action research. This research consists of 2 cycles of planning, implementation, observation, and reflection. The research subjects were 27 class IV students. The IPAS material used is